2010
DOI: 10.1111/j.1524-4725.2010.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus–Associated Lipohypertrophy (Buccal Fat Pad Lipoma-Like Lesions) Reduced with Subcutaneously Injected Sodium Deoxycholate

Abstract: Dr. Rotunda is the co-inventor of a patent that describes the use of deoxycholate as a method to treat localized fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Additional experiments have corroborated the lytic effects of DC on adipocytes in vivo and in vitro [49,50]. This laboratory and animal data has been validated through human studies that demonstrate comparable fat-reducing effects when either DC or PC/DC are injected into lipomas [40,31,44], abdominal [2,29], submental [3], and hip fat [2,3,29,40,41,30].…”
Section: Focus On DCmentioning
confidence: 50%
See 2 more Smart Citations
“…Additional experiments have corroborated the lytic effects of DC on adipocytes in vivo and in vitro [49,50]. This laboratory and animal data has been validated through human studies that demonstrate comparable fat-reducing effects when either DC or PC/DC are injected into lipomas [40,31,44], abdominal [2,29], submental [3], and hip fat [2,3,29,40,41,30].…”
Section: Focus On DCmentioning
confidence: 50%
“…A small, double-blind study investigating submental fat reduction demonstrated no differences in efficacy or safety of a low-concentration (1%) DC formulation compared to a PC (5%)/DC (4.75%) formulation. Low dose DC appears to be an efficacious and safe concentration for subcutaneous injection [3,31,44,56].…”
Section: Focus On DCmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional investigations by Dr. Rittes [28][29][30] and others [2,21,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have described using Lipostabil 1 , compounded PC/DC, and compounded DC only for fat reduction in the hips, abdomen, back rolls (known affectionately as ''love handles'' ( Fig. 3) in men or ''bra strap fat'' in women), dorsocervical region (''buffalo hump''), neck, jowls, and lipomas ( Fig.…”
Section: Lipostabil 1 and Lipodissolvementioning
confidence: 99%
“…8). The clinical relevance of this experimental work has been validated through studies that demonstrate comparable effects when either DC or PC/DC are injected into lipomas [38,43,44], abdominal [2,37], submental [3], and hip fat [2,3,[37][38][39]41].…”
Section: Isolation Of the Adipolytic Ingredientmentioning
confidence: 99%